1975
DOI: 10.1093/infdis/132.5.546
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of Heterophile and Epstein-Barr Virus-Specific IgM Antibody Tests in Clinical and Subclinical Infectious Mononucleosis: Specificity and Sensitivity of the Tests and Persistence of Antibody

Abstract: Three heterophile antibody tests and a test specific for IgM antibody to Epstein-Barr virus were evaluated during prospective studies of infectious mononucleosis. Specificity was judged by the frequency of false-positive results in sera of known qualities taken before illness; except for two patients bled during early, unrecognized illnes,, titers of greater than or equal to 1:40 were detected in 12% by the absorbed sheep red cell test, in 6.7% by the absorbed horse red cell test, and in none by the beef cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
1
7

Year Published

1976
1976
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(93 citation statements)
references
References 25 publications
3
82
1
7
Order By: Relevance
“…However, when the antibody response to individual viral polypeptides was determined by immunoblot, IgG and IgM reactivity to the EA polypeptides ~138 and ~45-52 was detectable in the first serum samples of all acutely infected IM patients (Middeldorp and Herbrink, 1988). Recently, Gorgievski-Hrisoho et al (1990) tested several recombinant EBV antigens, selected by Wolf et al (1985) and Motz et al (1986), with respect to reactivity among well-defined IM sera. It was shown, that particularly the EA proteins ~138 and p54 were excellently recognized by sera from patients with acute IM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when the antibody response to individual viral polypeptides was determined by immunoblot, IgG and IgM reactivity to the EA polypeptides ~138 and ~45-52 was detectable in the first serum samples of all acutely infected IM patients (Middeldorp and Herbrink, 1988). Recently, Gorgievski-Hrisoho et al (1990) tested several recombinant EBV antigens, selected by Wolf et al (1985) and Motz et al (1986), with respect to reactivity among well-defined IM sera. It was shown, that particularly the EA proteins ~138 and p54 were excellently recognized by sera from patients with acute IM.…”
Section: Discussionmentioning
confidence: 99%
“…Testing for heterophile antibodies is still widespread in routine diagnosis. However, despite the relatively high degree of specificity of the Paul-Bunnell agglutinins for the early stage of IM the test fails in some cases particularly with young children (Evans et al, 1975, Schmitz et al, 1972. Therefore, serodiagnosis of IM by measuring the specific antibody response is clearly to be preferred.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliance on the presence of HA and the hematological findings is the general practice for college students (4,12,14). Studies of patients with IM have shown that the majority have a positive test for HA and an absolute lymphocytosis, with 10% or more atypical cells (1,4,13,15,17,18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of patients with IM have shown that the majority have a positive test for HA and an absolute lymphocytosis, with 10% or more atypical cells (1,4,13,15,17,18,20). Evans and colleagues (4) found …”
Section: Discussionmentioning
confidence: 99%